The Charlemagne pursuit : a novel - Berry, Steve (New York : Ballantine Books, 2008)
A mysterious manuscript discovered in the tomb of Charlemagne sends Cotton Malone on a perilous international quest that takes him and twin sisters with their own agenda from an ancient German cathedral to the harsh, unforgiving world of Antarctica in pursuit of the truth about the death of his father on a classified sub mission beneath Antarctica.
Map on endpapers.
Keywords: Booksellers and bookselling--Fiction.; Antiquarian booksellers--Fiction.; Fathers--Death--Fiction.